Meningkatkan Indeks Maqashid Syariah melalui Pengelolaan Zakat untuk Pemberdayaan Ekonomi Umat - Abdul Jalil; Edo Segara Gustanto (Scimadly Publishing, 2023)
This article discusses the crucial role of zakat management in achieving the broader goals of Maqashid Syariah, especially in the context of economic empowerment of the people. Maqashid Sharia, which covers the maintenance of religion, life, reason, offspring, and wealth, plays an essential role in Islamic law and is the main guideline for achieving the prosperity of Muslim society. Zakat management is a vital tool in achieving the goals of Maqashid Syariah. Zakat, as one of the essential pillars of Islam, not only functions as a religious obligation but also as a vital instrument for empowering the people's economy. We investigate how Zakat can improve the Sharia Maqashid Index by focusing on economic aspects, including efforts such as micro-enterprises, education financing, skills training, and other productive initiatives. This article also presents case studies and real examples from communities and countries that have succeeded in incorporating Zakat in efforts to empower the economy of their people. Analysis of the impact of these cases reveals Zakat's great potential in achieving Maqashid Syariah's goals, such as more equitable and sustainable economic prosperity.